2018
DOI: 10.1016/j.csbj.2018.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Copper Chaperone Atox1 Interacts with Cell Cycle Proteins

Abstract: The anaphase-promoting complex (APC) is involved in several processes in the cell cycle, most prominently it facilitates the separation of the sister chromatids during mitosis, before cell division. Because of the key role in the cell cycle, APC is suggested as a putative target for anticancer agents. We here show that the copper chaperone Atox1, known for shuttling copper in the cytoplasm from Ctr1 to ATP7A/B in the secretory pathway, interacts with several APC subunits. Atox1 interactions with APC subunits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…In addition, a study by Dzebo and colleagues that showed Atox1 also interacts with anaphase‐promoting complex (APC). APC plays a critical role in cell cycle progression via degradation of cyclin‐dependent kinase 4 (CDK4); CDK4 and Cyclin D1 are both needed to promote S phase 32,33 . While these studies show a potential role for atox1 in the cell cycle, they are likely not an explanation for the arrest shown in the cell cycle analysis results.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, a study by Dzebo and colleagues that showed Atox1 also interacts with anaphase‐promoting complex (APC). APC plays a critical role in cell cycle progression via degradation of cyclin‐dependent kinase 4 (CDK4); CDK4 and Cyclin D1 are both needed to promote S phase 32,33 . While these studies show a potential role for atox1 in the cell cycle, they are likely not an explanation for the arrest shown in the cell cycle analysis results.…”
Section: Discussionmentioning
confidence: 84%
“…APC plays a critical role in cell cycle progression via degradation of cyclin-dependent kinase 4 (CDK4); CDK4 and Cyclin D1 are both needed to promote S phase. 32,33 While these studies show a potential role for (Figure 7). This result is consistent with those of a study that evaluated the effects of knocking out atox1 in breast cancer cells, showing increased time for wound-healing.…”
Section: Dc_ac50 Attenuates Migratory Ability Of Osa Cellsmentioning
confidence: 85%
“…In support for this hypothesis, a phase II clinical trial in triple negative breast cancer patients treated with the Cu chelator tetrathiomolybdate revealed that tumor microenvironment remodeling mediated through the Cu-dependent activity of LOX was ablated. 57,58 Finally, while several reports have suggested that ATOX1 regulates the expression of genes required for cell growth and proliferation by translocating to the nucleus, [51][52][53] ATOX1 is predominately localized to the cytosolic fraction of human melanoma cell lines (Fig. S2a, ESI †).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have reported that ATOX1 not only functions in the cytosol but also translocates to the nucleus to facilitate the transcription of genes like CCND1 to drive cell growth and proliferation. [51][52][53] We tested and found that ATOX1 is expressed at undetectable levels in several human cancer cell lines (HPAC and SW48) and an immortalized human cell line (HEK-HT) and is exclusively localized to the cytosolic fraction of A375 and WM88 melanoma cells (Fig. S2a, ESI †).…”
Section: Paper Metallomicsmentioning
confidence: 99%
“…Mammalian ATOX1 has been shown to be a copper-dependent transcription regulator; however, details of the functions of ATOX1 in these processes remain elusive ( Itoh et al , 2008 ; Muller and Klomp, 2009 ; Kahra et al , 2015 ; Kamiya et al , 2018 ; Matson Dzebo et al , 2018 ). Previous studies found that ATOX1 could directly bind the GAAAGA promoter sequence as a transcription factor ( Itoh et al , 2008 ; Muller and Klomp, 2009 ; Kamiya et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%